Regulation of atrial natriuretic peptide (ANP) and its role in blood pressure - Ahmed, Feroz; Tabassum, Nahida; Rasool, Saima (International Current Pharmaceutical Journal, 2012)
Atrial natriuretic peptide (ANP) a powerful vasodilator, and a protein (28-amino acid peptide) hormone secreted by heart muscle cells. It is released in response to atrial distention, stretching of the vessel walls, sympathetic stimulation of ?-adrenoceptors, raised sodium concentration, angiotensin-II and endothelin. ANP binds to three cell surface receptors called ANP receptors. The overall effect of ANP on the body is to counter increases in blood pressure and volume caused by the renin-angiotensin system. It has also been reported to increase the release of free fatty acids from adipose tissue. Regulation of its effects is achieved through gradual degradation of the peptide by the enzyme neutral endopeptidase (NEP). Inhibitors of NEP are currently being developed to treat disorders ranging from hypertension to heart failure. Synthetic analogs of ANP have been investigated as potential therapies for the treatment of decompensated heart failure and other diseases. DOI: http://dx.doi.org/10.3329/icpj.v1i7.10812 International Current Pharmaceutical Journal 2012, 1(7): 176-179